2008
DOI: 10.1002/micr.20483
|View full text |Cite
|
Sign up to set email alerts
|

Role of timing in assessment of nerve regeneration

Abstract: Small animal models are indispensable for research on nerve injury and reconstruction, but their superlative regenerative potential may confound experimental interpretation. This study investigated time-dependent neuroregenerative phenomena in rodents. Forty-six Lewis rats were randomized to three nerve allograft groups treated with 2 mg/(kg day) tacrolimus; 5 mg/(kg day) Cyclosporine A; or placebo injection. Nerves were subjected to histomorphometric and walking track analysis at serial time points. Tacrolimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 44 publications
1
76
0
3
Order By: Relevance
“…Processing for optical microscopy and transmission electron microscopy After 5 and 10 weeks of the surgical procedure [30,31], in each period, five animals in the control group and eight animals from each experimental group were euthanized with an Boverdose^of anesthesia to collect the intact buccal branch of the facial nerve from the control group and the distal stump from the buccal branch of the facial nerve in animals from the experimental groups.…”
Section: Laser Irradiationmentioning
confidence: 99%
“…Processing for optical microscopy and transmission electron microscopy After 5 and 10 weeks of the surgical procedure [30,31], in each period, five animals in the control group and eight animals from each experimental group were euthanized with an Boverdose^of anesthesia to collect the intact buccal branch of the facial nerve from the control group and the distal stump from the buccal branch of the facial nerve in animals from the experimental groups.…”
Section: Laser Irradiationmentioning
confidence: 99%
“…A recently described "blowthrough" effect in this animal model suggests that regardless of experimental variables, if too much time is allowed for nerve regeneration, enough axons will eventually regenerate to skew study outcomes. 24 The sweet spot between functional recovery and this blowthrough effect is still being worked out. We chose the 8-week recovery time used in this study to fall within this time range, although serial testing would be necessary to confirm this.…”
mentioning
confidence: 99%
“…At longer end points, it has been shown that the superlative regenerative capacities of rodents will mask real differences between treatment groups, with axonal counts eventually equalizing over time. 29 Having demonstrated early histological evidence of improved nerve regeneration, for the reasons mentioned earlier, follow-up studies using longer time points are now necessary to assess functional return. However, the results from this study serve to highlight the promise of chondroitinase as an agent to enhance nerve regeneration and functional outcomes after hand transplantation.…”
Section: Discussionmentioning
confidence: 98%